Access and achievement: Low-income students in Portuguese higher education case study - Justino, E.; Dias, D.; Santos, G. (International Journal of Higher Education, 2025)
This study investigates the experiences of low-income students in Portuguese higher education, focusing on universities in peripheral regions. Despite policies aimed at widening access since the 1980s, inequalities persist. The research examines whether families with greater social, cultural, and economic capital are disproportionately represented in higher education relative to their presence in Portuguese society. By analyzing class-based educational strategies employed by different social classes and their expectations of upward social mobility, the study conceptualizes access to higher education as a "game" of unequal opportunities. Using the University of Trás-os-Montes e Alto Douro (UTAD) in northern Portugal as a case study, the analysis combines statistical data with surveys of first-year students. Findings reveal the strong influence of socioeconomic background on access to higher education, underscoring the persistent selectivity and barriers faced by disadvantaged groups.